ANALISIS VISUAL GAMBAR ANAK PADA MASA PRA-SKEMATIK - Nuriarta, I Wayan; Krisna Ari, Ida Ayu Dwita; Suryawan, I Gde (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This article aims to read visual signs and verbal signs by utilizing the children's drawings during the pre-schematic stage. The reading of the signs will be used to describe the elements of fine arts in the children's drawing. Â Four works of kindergarten children were chosen and observed. The four works are entitled